School food programmes in the Pacific Islands: exploring opportunities and challenges for creating healthier school food environments - Sarah Burkhart; Ann Hayman; Fiasili Lam; Breanna Jones; Bridget Horsey; Dana Craven; Steven Underhill (Cambridge University Press, 2023)
Abstract Objective: The school setting can provide an environment that supports healthy behaviours, including the provision of food. School food activities, that is, school feeding, are commonplace globally, but not well understood in the Pacific Islands region. The aim of this research is to explore learnings associated within existing school food programmes (SFP), and adoption resistors in those Pacific Island Countries and Territories (PICT) without SFP, with the intent of improving current and future SFP interventions. Design: This observational cross-sectional study utilised four facilitated workshop sessions to explore SFP within an existing framework. Setting: Pacific Islands region. Participants: Fourteen participants representing the education and health sectors from eleven PICT, and two participants representing regional organisations. Results: Most countries reported some form of related policy, but key critical constraints to the use of SFP included local food environments, strategic alignment to organisational priorities, advocacy and organisational leadership, and community and cultural connections and collaboration. There are opportunities for integration of SFP into existing frameworks (i.e. Health Promoting Schools), increased collaboration, greater professional development and awareness activities, improved monitoring and evaluation, improved awareness of SFP and promotion of healthy eating for the wider school community. Conclusions: Given the current health, social and economic challenges faced by countries and territories in the Pacific Islands region, SFP should be considered as an opportunity for food provision and associated nutrition education for students and their wider community. Further research is needed to understand the critical constraints of SFP in this region and how to support stakeholders to advocate for, develop and sustain SFP that are contextually and culturally appropriate.